AB0679 One third of primary sjÖgren syndrome (PSS) patients with anti-CCP develop erosive rheumatoid arthritis (RA) after a 5-year follow-up. (23rd January 2014) - Payet, J.; Seror, R.; Gottenberg, J.-E.; Berger, E.; Desmoulins, F.; Meyer, O.; Mariette, X.
Abstract : Background: Rheumatologic manifestations affect 30 to 70% of pSS patients and present as recurrent and transient arthralgia or a real polyarthritis. These manifestations may sometimes be very similar to that of RA, but the presence of joint destruction and erosions is a specific hallmark of RA and help at distinguishing these 2 diseases. Anti-CCP antibodies are highly specific for the diagnosis of RA but were found in other systemic diseases. In pSS, their prevalence is about 5 to 10%. Objectives: To follow patients with pSS and anti-CCP during more than 5 years to establish frequency and predictors of evolution to RA. Methods: A retrospective, observational, multicentric study was performed including all patients having pSS and anti-CCP and having a follow-up of more than 5 years in 2 French rheumatology departments. At diagnosis, patients met AECG criteria for pSS diagnosis, but did not meet ACR 1987 criteria for the diagnosis of RA. At inclusion, collected data were: demographic; clinical data about articular manifestations, sicca syndrome and systemic involvement; immunological and radiological data. Hand and feet X-rays were systematically performed 5 years after inclusion. During follow-up, diagnosis of RA was done in case of appearance of bone erosions on foot or hand X-rays Results: In all, 16 patients were included in the study: 14 (87.5%) were women, median age was 52 (33 to 71) years, 10 (62.5%) patients had arthralgia and 7 (43.7%) had arthritis at diagnosis. Subjective xerostomia was present in 15 patients (93.7%) and subjective xerophtalmia in 14 patients (87.5%). Anti-SSA antibodies were found in 10 patients (62.5%) and anti-SSB in 6 patients (37.5%). After a median follow-up of 8 (5 to 10) years, 11 patients were still considered as having a pSS and 5 patients developed a real erosive RA. Anti-CCP persisted at 5 years in all patients but one in whom the initial anti-CCP level was 50 IU. In univariate analysis, predictors of evolution to RA were high ESR (p=0, 037) and high CRP (p=0, 033) at diagnosis. In multivariate analysis, only ESR was associated to an increased risk of developing erosive RA. Conclusions: Although it is established that 5-10% of pSS patients have anti-CCP, one-third of them might develop a true RA. A close monitoring of these patients seems necessary to look for erosive changes that indicate a pejorative evolution and might require more active treatment. Disclosure of Interest: None Declared